The effect of premature mortality due to despair on life expectancy in Brazil - Raphael Mendonça Guimarães; José Henrique Costa Monteiro-da-Silva (Revista Brasileira de Epidemiologia)
ABSTRACT Objective: The aim of this study was to estimate the impact of deaths of despair (DoD) on life expectancy at birth and by sex in Brazil in 2019, as well as the contribution of different age groups to this loss. Methods: We used life tables from the Brazilian Institute of Geography and Statistics and cause-specific mortality data by age and sex from the Mortality Information System. A cause-deleted life table methodology was applied, assuming independence between DoD and other causes of death. The difference in life expectancy with and without DoD was decomposed by age using Arriaga’s method. DoD included deaths from suicide, intentional or accidental poisoning, and mental and behavioral disorders due to substance use. Results: In 2019, there were 23,391 DoD in Brazil (1.73% of all deaths), 89% of which were due to suicide. Removing these deaths would increase life expectancy by 0.43 years for men and 0.12 years for women, with men experiencing a 3.5 times greater impact. The 35-49 age group had the highest relative contribution, especially among men, where DoD accounted for up to 9.7% of the loss in life expectancy. The impact was more concentrated and earlier in men and more diffuse among women. Conclusion: Although lower in absolute numbers, DoD have a measurable impact on life expectancy, especially among young men. These findings highlight the need for public policies focused on suicide prevention and addressing the social determinants that sustain despair.